FACEBOOK CONTENTS AND JOB RECRUITMENT: AN EXPERIMENTAL STUDY - Febby Erianto Nugroho; Irwan Trinugroho (Universitas Mercu Buana, 2018)
Abstract. This paper presents an experimental study exploring the effect of Facebook applicants' content on the recruitment decisions made by job recruiters. Facebook content is divided into professional and non-professional contents. We employ 40 participants in this experimental design. Our results show that the applicants’ Facebook contents significantly affect the recruitment decisions which is indicated by the difference of choice from the first phase to third phase. Qualified applicants are associated with more professional contents on their Facebook accounts.